The level of nutritional and health awareness among female athletes in Jordan - Jawarneh, Randa Saleh; Obeidat, Lubna Mahmoud; Al-Momani, Mohammad Omar; Theiyabat, Emadeddln Mohammad (Intelektual Pustaka Media Utama, 2024)
The study aimed to identify women's awareness levels in Jordan about food nutrition and health due to the importance of her being the head of the family and directly responsible for feeding the entire family. Starting with the child and the rest of the family members, where the descriptive approach was used, which was done through the use of a questionnaire that consisted of seven domains as a tool for the study, which was applied to a sample of (1,000) married women from the governorates of Ajloun, Irbid, Jerash, Mafraq, and the capital, Amman, who was selected in a simple random way. Where the study concluded, that the general level of nutritional and health awareness for women was average. In addition, their level of awareness was low in the following areas: (carbohydrates, fruits, and vegetables, children's nutrition, while moderate in adult nutrition, milk, and its products, proteins, and pregnant women's nutrition. The study also found that there is a positive and significant correlation between the level of women's awareness and their subjective factors represented by (their level of education, economic status, children's education, cultural contact, and husband's education), while the correlation was negative and significant with (age and number of children).